Boehmian spaces for a class of Whittaker integral transformations - shrideh al-omari (Kuwait Journal of Science)
In this paper, we are concerned with a class of Whittaker integral transforms involving confluent hypergeometric functions as kernels. We present certain convolution products and derive the prerequisite axioms for generating the relevant spaces of Boehmians. We further give the definition and discuss the inverse problem of the Whittaker integral in a generalized sense. Moreover, the integral in question has been shown to be linear and consistent with the classical one. Certain results are also discussed in some details.